Civil Society’s Dual Role in Foreign Policy: A Comparative Analysis of Benefits and Risks - Naldo Helmys; Yurisa Irawan (JURNAL HUBUNGAN LUAR NEGERI, 2024)
This paper examines the role of civil society as an instrument of foreign policy, exploring its potential benefits and risks. Traditionally, foreign policy analysis focused on decision-making processes and the primacy of the state. However, the end of the Cold War, the rise of post-positivist approaches, and the increasing interconnectedness of global issues have led to a broader consideration of policy instruments, including the involvement of non-state actors like civil society. The study employs a comparative approach to analyze the benefits of civil society in promoting democracy and addressing global challenges against the risks of biased utilization and dependency on state support. It examines case studies, including the role of USAID in Myanmar and the Israel-Palestine conflict, as well as the Indonesian context, where the government engages civil society in development and foreign policy. The findings highlight the need for a balanced approach that leverages civil society’s strengths while mitigating its risks as an instrument of foreign policy.